Observation of the c‐f hybridization effect in valence‐transition system EuPtP. Issue 6 (1st March 2017) - Anzai, Hiroaki; Ichiki, Katsuya; Schwier, Eike F.; Iwasawa, Hideaki; Arita, Masashi; Sato, Hitoshi; Shimada, Kenya; Namatame, Hirofumi; Taniguchi, Masaki; Mitsuda, Akihiro; Wada, Hirofumi; Mimura, Kojiro
Abstract : We study the electronic structure of EuPtP, which exhibits two first‐order valence transitions at T 1 = 247 K and T 2 = 201 K, using angle‐resolved photoemission spectroscopy. Below T 2, we observe an energy gap at the crossing point of the bulk Eu 4 f and conduction bands. The shape of band dispersions is described by a hybridization‐band picture based on the periodic Anderson model. Our results demonstrate the c ‐ f hybridization effect in the low‐temperature phase of EuPtP.